Alteration of light-dependent gene regulation by the absence of the RCO-1/RCM-1 repressor complex in the fungus Neurospora crassa. - Carmen Ruger-Herreros; María del Mar Gil-Sánchez; Gencer Sancar; Michael Brunner; Luis M Corrochano (PLoS ONE, 2014)
The activation of transcription by light in the fungus Neurospora crassa requires the White Collar Complex (WCC), a photoreceptor and transcription factor complex. After light reception two WCCs interact and bind the promoters of light-regulated genes to activate transcription. This process is regulated by VVD, a small photoreceptor that disrupts the interaction between WCCs and leads to a reduction in transcription after long exposures to light. The N. crassa RCO-1/RCM-1 repressor complex is the homolog of the Tup1-Ssn6 repressor complex in yeast, and its absence modifies photoadaptation. We show that the absence of the RCO-1/RCM-1 repressor complex leads to several alterations in transcription that are gene-specific: an increase in the accumulation of mRNAs in the dark, a repression of transcription, and a derepression of transcription after long exposures to light. The absence of the RCO-1/RCM-1 repressor complex leads to lower VVD levels that are available for the regulation of the activity of the WCC. The reduction in the amount of VVD results in increased WCC binding to the promoters of light-regulated genes in the dark and after long exposures to light, leading to the modification of photoadaptation that has been observed in rco-1 and rcm-1 mutants. Our results show that the photoadaptation phenotype of mutants in the RCO-1/RCM-1 repressor complex is, at least in part, an indirect consequence of the reduction of vvd transcription, and the resulting modification in the regulation of transcription by the WCC.